Comparative study of superparamagnetic iron oxide/doxorubicin co-loaded poly (lactic-co-glycolic acid) nanospheres prepared by different emulsion solvent evaporation methods. (18th August 2018) - Mosafer, Jafar; Teymouri, Manouchehr
Abstract: Poly (lactic-co-glycolic acid) (PLGA) is a widely used biodegradable polymer for preparation of polymeric biodegradable carriers that shows attractive features and offers possibilities to tune the physicochemical characteristics, drug release properties and biological behaviour of the PLGA-based nanospheres. Double emulsion solvent evaporation methods fail when it comes to encapsulation of highly hydrophilic drugs such as doxorubicin (Dox). The reason for this defect is due to the rapid drug diffusion into the external aqueous phase before solidification of the PLGA nanospheres. In this study, we present a comprehensive comparison between the four different fabrication methods of PLGA nanospheres with a focus on double emulsion solvent evaporation-based methodologies to achieve the effective method for co-encapsulation of superparamagnetic iron oxide nanoparticles (SPIONs) and Dox into the PLGA polymer in terms of the size of nanoparticles, particle size distribution and drug loading. Therefore, the optimized ratio of the different phases and other process parameters of these methods is discussed. In conclusion, the prepared SPIO/Dox-PLGA nanospheres (NPs) via a modified double emulsion solvent evaporation method were found to be a promising delivery system in terms of particle size distribution, drug loading, release profile as well as magnetic properties for tumour therapeutic and diagnostic purposes.